One-year clinical performance of self-etch adhesives in posterior restorations - Perdigao, Jorge; Dutra-Correa, Maristela; Castilhos, Natalia; Carmo, Andre R. P.; Anauate-Netto, Camillo; Cordeiro, Hiram J. D.; Amore, Ricardo; Lewgoy, Hugo R. (Mosher & Linder, Inc, 2007)
Purpose: To evaluate the 1-year clinical performance of three self-etching adhesives (Adper Prompt L-Pop, Clearfil S-3 Bond, iBond) in posterior composite restorations using one etch&rinse adhesive (One-Step Plus) as control. Methods: Upon approval by the Institutional Review Board, 121 restorations were inserted in 38 subjects. The adhesives were applied as per manufacturers' instructions. Preparations were restored with a nanofilled resin composite (Filtek Supreme) and evaluated at baseline, 6 months, and 1 year. Statistical analyses included the Chi-square distribution with the McNemar non-parametric test (P< 0.05). Results: At 1 year, 111 restorations in 35 subjects were evaluated using the USPHS modified criteria. No significant changes were observed for the etch&rinse adhesive One-Step Plus. At 1 year the number of Alfa ratings decreased significantly for Clearfil S-3 Bond and for iBond in the categories color match, marginal staining, and marginal adaptation. For Adper Prompt L-Pop, marginal adaptation at 1 year was significantly worse than at baseline. Postoperative sensitivity to air improved significantly for Adper Prompt L-Pop, Clearfil S-3 Bond, and iBond. When the evaluation criteria were paired at 1 year, iBond resulted in a significantly lower number of Alfa ratings than any of the other adhesives for color match, marginal staining, and marginal adaptation. One-Step Plus resulted in a greater number of Alfa ratings for marginal adaptation than either Adper Prompt L-Pop or Clearfil S-3 Bond. Marginal adaptation was significantly better for Clearfil S-3 Bond than for Adper Prompt L-Pop. The post-operative sensitivity measured at 1 year for Adper Prompt L-Pop was statistically better than that for One-Step Plus.